Comparison of the effectiveness of group therapy-based psychodrama and transactional analysis on conflict with parents of male adolescents - ali akbar zare; mohammad ghamari; ghorban fatheaghdam; mojtaba amirimajd (مجله علوم روانشناختی)
Background: Considering that adolescence is one of the most sensitive stages of human development, special attention should be paid to solving the educational and psychological problems of this group. One of the best strategies in this regard is to use psychological interventions. Aims: This study aimed to compare the effectiveness of psychodrama-based group therapy and transactional analysis on conflict with parents of male adolescents. Methods: This semi-experimental study was performed based on a pre-test, post-test, and follow-up design with a control group. The study population consisted of all third-grade male students of the first period of ordinary public high schools in Khorramdareh in the academic year of 2019-2020. In total, 30 Male students were selected using the available sampling and randomly divided into three groups. Members of both experimental groups received their treatment in eight 1.5-hour sessions. The research tool was the adolescent conflict questionnaire with Prince's parents. The findings were analyzed through repeated measures ANOVA and Bonferroni post-hoc test. Results: The mean and standard deviation of conflict with mother and conflict with father of the psychodrama group in the pre-test (28.10±2.37 and 28.70±1.82), transactional analysis group (28.60±2.55 and 28.20±1.98), and control group (27.60±2.17 and 27.60±1.77) respectively. Psychodrama (24.10±2.13 and 24.80±2.90) and transactional analysis (24.00±2.90 and 25.30±2.33) compared to the control group (27.80±2.04 and 27.90±1.91) reduced the conflict with mother (p<0.001) and the conflict with father in the post-test (p<0.001). In the follow-up phase, the effect of psychodrama (24.40±2.11 and 26.10±1.91) and transactional analysis (24.40±2.75 and 25.20±1.13) on conflict with mother and conflict father (28.40±2.31 and 27.90±1.91) (p<0.001; p<0.001). The effect of psychodrama and transactional analysis on conflict with the mother and conflict with the father was the same in the post-test and follow-up stages (p>0.05). Conclusion: Psychodrama has been effective in reducing conflict with parents by utilizing the art of communication reconstructing situations and evacuating emotions, and transactional analysis of behavior by providing a picture of psychological structure and helping how to behave effectively.